(3TQM cdjGJ GdbGfhf aj GdWH dGHf SjfGs - (3bWH GdOjf , eMehO Hf eSYhO GdSjQGRis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3CeG HYO aGf eMehO Hf eSYhO GHf eUdM GdTjQGRi , jbhd deG cGf CYPH eTGQH GdfYe s
(3BNQgG (B:s
(3JfJgi HTQM bhd GHf SjfG hef GdfGS ef jXf Cf bhI GdHOf JGHYI dcKQI GdOe hVYaI JGHY dbJdg , hdjS cPdc s
(3bWYI JHOC HChd GdTQMs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B115 s
Keywords: (3GdWHs